Deep Learning-Based Curriculum Innovation in Islamic Religious Education: A Human Resource Development Strategy in the Industrial Revolution 5.0 Era - Redy Eka Yudesthira; Achmad Alfaridzih; Ahmad Luqman Hakim (al-Afkar, Journal For Islamic Studies, 2026)
The Industrial Revolution 5.0 demands that the education sector, including Islamic Religious Education (PAI), innovate its curriculum to equip students with a balanced set of spiritual, social, and technological competencies. This study aims to analyze deep learning-based PAI curriculum innovations as a strategy for human resource development in the era of the 5.0 Industrial Revolution, with reference to the three main pillars of deep learning: meaningful learning, mindful learning, and joyful learning. The study employs a qualitative descriptive approach with a multiple-case design conducted at two schools: MTs Nur Rahmat Dukun and SMP IT Al Uswah Tuban. Data were collected through unstructured interviews, passive participant observation, and documentation, and were subsequently analyzed using the Miles, Huberman, and Saldana model. The results indicate that both schools implement the three pillars of deep learning in a contextual and adaptive manner, tailored to their respective characteristics. MTs Nur Rahmat Dukun tends to link course material to daily life through a simple contextual approach, while SMP IT Al Uswah Tuban integrates the national curriculum, SIT, and Kemenag curricula using a tauhid-based approach alongside a boarding system that fosters greater independence in learning. These differences in strategy do not represent disparities but rather forms of differentiation that strengthen the effectiveness of students’ competency development. This study confirms that an integrative deep learning approach can be an effective strategy for developing adaptive and reflective human resources in the era of the 5.0 industrial revolution.